Systematic Literature Review Application of Transferable Skills As A Key Factor For Vocational School Graduates - Yuliyanto, Riyan; Susilaningsih, Susilaningsih; Indriayu, Mintasih (Program Studi Pendidikan Ekonomi FKIP Universitas Lambung Mangkurat, 2024)
The gap between the competence of vocational school graduates and employers' expectations results in high unemployment among vocational school graduates. Therefore, vocational education needs to develop transferable skills to create a workforce ready to face the demands of the modern job market. This systematic literature review explores the importance of transferable skills and their impact on vocational schools. This study focused on scientific articles published between 2014-2023 using the Scopus database. This review identifies a growing body of literature that emphasizes the importance of equipping students with competencies that are not only relevant to their specific tasks but also valuable across a range of Occupational contexts. The increase in publications in 2023 indicates an increased scientific interest. The focus of research that is widely studied is curriculum, practical learning, extracurricular, and lifelong learning. Collaboration strategies between educators, institutions, and industry partners in developing responsive and relevant curricula will support the development of transferable skills. Then, in the end, the study also proposes future research topics.